Countering Social and Cultural Constructs Towards Women: Realizing Gender Justice in The Household - Yulianti Yulianti; Nadya Kharima (International Seminar on Social Work Update, 2023)
The social and cultural constructions that develop in society have been formed so that there is an assumption that a mother is the most responsible person in the upbringing of children. But basically childcare is a shared responsibility between husband and wife.  Even though the mother is the first school for her children, the father also has a great responsibility in the upbringing of the child.  Then, mothers are not only given great responsibility in childcare, social and cultural constructions in Indonesia form that a wife or mother must be able to do housework and the husband is responsible for providing a living. The purpose of this study, researchers want to see how a mother eliminates the constructions that develop in society in realizing gender justice and equality in the household. The research method in this study is a descriptive qualitative method because it is to discuss the research results comprehensively. Data collection in this study used interviews with two young mothers.  The results in this study show that in realizing gender justice in the household, each couple must prepare for marriage in terms of science and mentality so that each other understands each other regarding their respective roles and responsibilities. responsible for childcare and domestic work. and the establishment of a culture of communication in carrying out the division of roles in order to the emergence of justice in the household